2015
DOI: 10.1007/s15010-015-0863-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of blood culture-negative endocarditis and clinical comparison between blood culture-negative and blood culture-positive cases

Abstract: BCNE resulted mostly from prior antibiotics and was associated with severe hemodynamic compromise. Valve histopathology and PCR were useful in confirming the diagnosis and pointing to the etiology of BCNE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 40 publications
5
46
2
10
Order By: Relevance
“…Compared to the literature published from China on IE, the rate approached to other studies in our region [14][15][16]. But it was signi cantly lower than that reported by other studies from developed countries with 74%-100% [26,27].However, according to the 2015 European Association of Cardiology guidelines on IE , for TTE positive patients, TEE should be performed to exclude perivalvular complications [1]. The low utilization rate of TEE could directly resulted in the low detection rate of perivalvular complications such as valvular perforation and perivalvular abscess.…”
Section: Discussioncontrasting
confidence: 75%
“…Compared to the literature published from China on IE, the rate approached to other studies in our region [14][15][16]. But it was signi cantly lower than that reported by other studies from developed countries with 74%-100% [26,27].However, according to the 2015 European Association of Cardiology guidelines on IE , for TTE positive patients, TEE should be performed to exclude perivalvular complications [1]. The low utilization rate of TEE could directly resulted in the low detection rate of perivalvular complications such as valvular perforation and perivalvular abscess.…”
Section: Discussioncontrasting
confidence: 75%
“…Based on a review of the literature published from China on IE, the rate was similarly but it approached to other studies in our region [13,18,19]. But this rate was significantly lower than that reported by other studies from developed countries with 74%-100% [20,21].However, according to the 2015 European Association of Cardiology guidelines on IE, for TTE positive patients, TEE should be performed to exclude perivalvular complications[1]. The low utilization rate of TEE could directly resulted in the low detection rate of perivalvular complications such as valvular perforation and perivalvular abscess in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Gram stain of tissue processed in the microbiology laboratory may be more sensitive than histopathological Gram stain of tissue sections, 81% versus 67% in one study; however, in 10% of cases, the histopathology Gram stain detected organisms while the microbiology Gram stain was negative (17). Unfortunately, several studies have shown that culture of valve tissue suffers from low sensitivity and specificity, with positive cultures in only 6% to 26% of endocarditis cases (17,18,25). A microorganism different from that identified by blood culture or valve PCR was detected in 36% (10/28) of positive valve cultures in one study, suggesting a high rate of false positivity of valve culture (25).…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 91%
“…Blood cultures are negative in 2% to 40% of cases of endocarditis, with some studies reporting blood culture-negative rates up to 71% (4,5,(17)(18)(19). The causes of so-called "culture-negative endocarditis" fall into two categories: negative blood cultures due to concomitant or antecedent antibacterial therapy or the presence of an organism that does not grow in routine blood cultures, with the first being more common.…”
Section: Diagnosis Of Culture-negative Endocarditismentioning
confidence: 99%